2001
DOI: 10.1046/j.0014-2956.2001.02502.x
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding and refolding studies of frutalin, a tetrameric d-galactose binding lectin

Abstract: Protein refolding is currently a fundamental problem in biophysics and molecular biology. We have studied the refolding process of frutalin, a tetrameric lectin that presents structural homology with jacalin but shows a more marked biological activity. The initial state in our refolding puzzle was that proteins were unfolded after thermal denaturation or denaturation induced by guanidine hydrochloride, and under both conditions, frutalin was refolded. The denaturation curves, measured by fluorescence emission,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…An exception to this is the case of frutalin, which shows a DG A of only À6 kcal mol À1 (dimer units). Nonetheless, the actual stability of frutalin corresponds to that of the tetramer, as this oligomer forms from the unfolded free subunits in an all-or-none process (39). In fact, this formation mechanism and high structural stability are not surprising for proteins that require the oligomeric state to perform their biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…An exception to this is the case of frutalin, which shows a DG A of only À6 kcal mol À1 (dimer units). Nonetheless, the actual stability of frutalin corresponds to that of the tetramer, as this oligomer forms from the unfolded free subunits in an all-or-none process (39). In fact, this formation mechanism and high structural stability are not surprising for proteins that require the oligomeric state to perform their biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescence emission spectrum of the purified recombinant frutalin showed an emission maximum at 335 nm. Native frutalin presents a fluorescence emission maximum at 333 nm [7].…”
Section: Sugar Binding Studiesmentioning
confidence: 99%
“…Protein concentration was determined by Bradford's method and the purity of frutalin in solution was confirmed by the presence of only two bands (~15.5 kDa and~12 kDa) after SDS-PAGE. The hemagglutinating effect of frutalin against human erythrocytes (O group) was determined as described [20] and the lectin showed hemagglutinating on activity at 0.2 Ag/ml (minimum dose capable of agglutinating 2% erythrocyte suspension).…”
Section: Frutalin Purificationmentioning
confidence: 99%
“…Frutalin, an a-d-galactose-binding lectin purified from Artocarpus incisa seeds, shares many structural characteristics with jacalin [19]. Physical-chemical and biological studies have shown that frutalin possessed presented hemagglutinating activity greater than jacalin [20]. More recently, we have demonstrated that interaction of frutalin with human neutrophils induced chemotaxis and triggered the oxidative burst.…”
Section: Introductionmentioning
confidence: 95%